2022
DOI: 10.1002/cre2.640
|View full text |Cite
|
Sign up to set email alerts
|

Does high sugar intake really alter the oral microbiota?: A systematic review

Abstract: Objectives: Diet is one of the main factors influencing the diversity and interactions of the oral microbiota. The purpose of this study is to determine the impact of sugar intake on the microbial diversity and bacteria that predominate under these conditions.Material and Methods: A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guide, using the PubMed, Scopus, and Science Direct databases and combinations of the words "microbiota," … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…This finding is in accordance with the ecological plaque hypothesis [ 15 ], in which frequent sugar consumption is considered the critical external perturbation, as this promotes favorable living conditions for aciduric and acidogenic species at expense of health-associated species, thereby leading to loss of diversity and potentially to the development of dental caries [ 16 , 17 ]. The finding is further supported by previous studies comparing individuals with different levels of sugar intake, which also found significantly lower diversity among individuals with a high sugar intake [ 6 ]. Interestingly, cross-sectional data have previously shown that samples from surfaces with dental caries are characterized by lower diversity compared to samples from healthy supragingival sites [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in accordance with the ecological plaque hypothesis [ 15 ], in which frequent sugar consumption is considered the critical external perturbation, as this promotes favorable living conditions for aciduric and acidogenic species at expense of health-associated species, thereby leading to loss of diversity and potentially to the development of dental caries [ 16 , 17 ]. The finding is further supported by previous studies comparing individuals with different levels of sugar intake, which also found significantly lower diversity among individuals with a high sugar intake [ 6 ]. Interestingly, cross-sectional data have previously shown that samples from surfaces with dental caries are characterized by lower diversity compared to samples from healthy supragingival sites [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, cross-sectional data show that the salivary microbiota differs significantly in individuals with different levels of sugar intake [ 5 ]. The supragingival microbiota in individuals with a high sugar intake is characterized by less diversity and a higher abundance of Actinomyces , Rothia, Lactobacillus, Veillonella , and Streptococcus species compared to individuals with a low sugar intake [ 5 , 6 ]. Previous data highlight that the acidogenic and aciduric members of the oral microbiota thrive when the oral ecosystem is exposed to carbohydrates, but interventional studies are needed to reveal the direct impact of frequent sugar intake on the oral ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…A diet is one of the factors affecting the diversity and interactions of the oral microbiota 45 . It has been proved that the diet is a factor which modifies e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of a link between oral dysbiosis and disease, namely periodontitis and IBD [ 48 , 49 ], with many oral commensals detected in the lower GI tract in IBD [ 48 ]. Moreover, many of these bacteria are opportunistic pathogens and sugar-rich diets fuel oral dysbiosis and the emergence of pathogens [ 50 , 51 ]. Interestingly, the black module showed a trend towards a negative association with MDS and a positive association with FCP but did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%